Refashioning pop music in Asia : cosmopolitan flows, political tempos, and aesthetic industries - Chun, Allen John Uck Lun, 1952-; Rossiter, Ned; Shoesmith, Brian (RoutledgeCurzon, 2004)
This collection of thirteen essays examines cultural, political, economic, technological and institutional aspects of popular music across Asia, from India to Japan.
Keywords: Popular music -- Asia -- History and criticism.; Popular music -- Social aspects -- Asia.; Popular music -- Political aspects -- Asia.; Musique populaire -- Asie -- Histoire et critique.; Musique populaire -- Aspect social -- Asie.; Musique populaire -- Aspect politique -- Asie.; MUSIC -- Genres & Styles -- International.; MUSIC -- Genres & Styles -- Pop Vocal.; MUSIC -- Genres & Styles -- New Age.; Popular music; Popular music -- Political aspects; Popular music -- Social aspects; Asia; Criticism, interpretation, etc.